2018
DOI: 10.1186/s12859-018-2017-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving prediction of heterodimeric protein complexes using combination with pairwise kernel

Abstract: BackgroundSince many proteins become functional only after they interact with their partner proteins and form protein complexes, it is essential to identify the sets of proteins that form complexes. Therefore, several computational methods have been proposed to predict complexes from the topology and structure of experimental protein-protein interaction (PPI) network. These methods work well to predict complexes involving at least three proteins, but generally fail at identifying complexes involving only two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The convolutional base includes three significant types of layers are: convolutional layers [31] , activation layers [32] , and pooling layers [33] . These types of layers are used to discover the basic features of input images, which are called feature maps.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…The convolutional base includes three significant types of layers are: convolutional layers [31] , activation layers [32] , and pooling layers [33] . These types of layers are used to discover the basic features of input images, which are called feature maps.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…1C ). This observation has led to the design of algorithms to identify sparse ( Srihari and Leong, 2012 ; Yong et al , 2012 ) as well as small complexes ( Ruan et al , 2018 ; Yong et al , 2014 ), which have slightly improved the recall of protein complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, comparative analyses have demonstrated that these approaches are not able to predict high-confidence clusters and suffer from small recall [33] . This observation has led to the design of algorithms to identify sparse [34] , [35] and small complexes [36] , [37] , which have slightly improved the recall of protein complexes. Yet, these algorithms depend on multiple parameters, which render it difficult to gauge the performance in absence of optimal parameter values for different combinations of PPI networks and gold standards.…”
Section: Introductionmentioning
confidence: 99%